Poor development of the listening skill and its incidence in english learning process for students of the ninth courses, Vespertine Section at the Juan Montalvo High School, during 2007-2008 - Sarmiento Chugcho, Kleber Oswaldo (2008)
This research aims to find the reasons for the poor development of the listening skill in the teaching-learning process. It has as only purpose to suggest strategies which helps to improve the listening skill teaching. This research is analytic-descriptive and proposal and the methodology will be explained in the methodological design. The setting problem will help us to elaborate the system problem-objectives and hypothesis. Once the variables worked out which take part in each hypothesis, the data collection process will begin and it will allow the demonstration of the same ones. The achievement of empiric information requests the necessity to identify and select the investigation units and the procedure to establish their quantification, selected the investigation units I will proceed to design the instruments for data collection and their consistency will be proved by means of the monitoring. Once achieved the collection and processing data, each one of the elements will be analyzed and interpreted quanti-qualitatively and described, in their particularities. The analysis axes will be the studied variables presented in the objectives and the hypotheses, the frequencies or highest percentages will be considered to elaborate conclusions and the proposal will be elaborated, taking as input the results of the investigation.